2015
DOI: 10.5348/ijcri-201502-ed-10002
|View full text |Cite
|
Sign up to set email alerts
|

Management of Inflammatory breast cancer: current concepts

Abstract: International Journal of Case Reports and Images (IJCRI) is an international, peer reviewed, monthly, open access, online journal, publishing high-quality, articles in all areas of basic medical sciences and clinical specialties.Aim of IJCRI is to encourage the publication of new information by providing a platform for reporting of unique, unusual and rare cases which enhance understanding of disease process, its diagnosis, management and clinico-pathologic correlations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A common question raised with respect to performing breast-conserving therapy after neoadjuvant chemotherapy is the volume of breast tissue that should be resected. To evaluate this, Boughey et al studied [4] whether preoperative chemotherapy was able to reduce the volume of tissue excised and the number of breast operations performed and reported that in patients with T2 or T3 tumors, significantly less tissue was resected when patients received neoadjuvant chemotherapy (P < .004 for volume of tissue resected). At a median followup time of 33 months there were only two cases of ipsilateral breast recurrence, one in the neoadjuvant group, and one in the adjuvant group, leading them to conclude that it is not necessary to excise the entire pre NACT volume of tissue.…”
Section: Editorialmentioning
confidence: 99%
“…A common question raised with respect to performing breast-conserving therapy after neoadjuvant chemotherapy is the volume of breast tissue that should be resected. To evaluate this, Boughey et al studied [4] whether preoperative chemotherapy was able to reduce the volume of tissue excised and the number of breast operations performed and reported that in patients with T2 or T3 tumors, significantly less tissue was resected when patients received neoadjuvant chemotherapy (P < .004 for volume of tissue resected). At a median followup time of 33 months there were only two cases of ipsilateral breast recurrence, one in the neoadjuvant group, and one in the adjuvant group, leading them to conclude that it is not necessary to excise the entire pre NACT volume of tissue.…”
Section: Editorialmentioning
confidence: 99%
“…To evaluate this, Boughey et al studied [4] whether preoperative chemotherapy was able to reduce the volume of tissue excised and the number of breast operations performed and reported that in patients with T2 or T3 tumors, significantly less tissue was resected when patients received neoadjuvant chemotherapy (P < .004 for volume of tissue resected). At a median followup time of 33 months there were only two cases of ipsilateral breast recurrence, one in the neoadjuvant group, and one in the adjuvant group, leading them to conclude that it is not necessary to excise the entire pre NACT volume of tissue.…”
Section: Editorialmentioning
confidence: 99%